2000
DOI: 10.1089/15246090050200042
|View full text |Cite
|
Sign up to set email alerts
|

A Profile of Early Versus Late Onset of Obesity in Postmenopausal Women

Abstract: Obesity is a serious health problem among women across the life span. Although people can become obese at any age, there is a large proportion of older women who have been obese since childhood. The purpose of this study was to determine whether postmenopausal women with an early versus late onset of obesity manifested differences in body habitus, eating behaviors, and mood. One hundred thirty-five postmenopausal women with obesity responded to self-report questionnaires on weight history, weight loss and main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 22 publications
2
7
1
1
Order By: Relevance
“…Taking these intercorrelations into account, binge eating severity, dietary restraint, and the frequency of fantasizing a lot about favorite foods appeared to be particularly important independent correlates of obesity. These results are consistent with previous findings that have shown that sex and race-ethnicity are important factors influencing body weight (35), and that higher BMI is correlated with early onset of obesity (36), repeated attempts at dieting (37), lower self-efficacy (3), low levels of dietary restraint (6 -8), emotional eating (25,38,39), and binge eating (40,41). The current results also confirm the relations between higher BMI and levels of perceived stress (4,5) and demonstrate new associations between BMI and stage of change related to weight loss, feeling deprived while dieting, and fantasizing a lot about favorite foods while dieting.…”
Section: Psychological and Behavioral Variablessupporting
confidence: 93%
“…Taking these intercorrelations into account, binge eating severity, dietary restraint, and the frequency of fantasizing a lot about favorite foods appeared to be particularly important independent correlates of obesity. These results are consistent with previous findings that have shown that sex and race-ethnicity are important factors influencing body weight (35), and that higher BMI is correlated with early onset of obesity (36), repeated attempts at dieting (37), lower self-efficacy (3), low levels of dietary restraint (6 -8), emotional eating (25,38,39), and binge eating (40,41). The current results also confirm the relations between higher BMI and levels of perceived stress (4,5) and demonstrate new associations between BMI and stage of change related to weight loss, feeling deprived while dieting, and fantasizing a lot about favorite foods while dieting.…”
Section: Psychological and Behavioral Variablessupporting
confidence: 93%
“…The incidence of depression in our study was much higher than the 8% recently reported in obese patients with a mean BMI of 36 kg/m 2 . 38 McCrone et al found a positive correlation between earlier onset of obesity and the presence of an affective disorder in women, 42 but this was not seen in our population. Over 22% of those examined demonstrated personality features commonly found in individuals with eating disorders, and 11.5% had a score for bulimia within or above the eating disorder range.…”
Section: Discussioncontrasting
confidence: 74%
“…39,40 Individuals who reported an earlier onset of obesity were also more obese at presentation, consistent with previous studies. 41,42 An earlier onset of obesity was not associated with more impairment of quality of life, but this may have been difficult to detect, due to the uniformly high levels of impairment reported by many individuals. In fact a later onset of obesity was associated with more impairment in work-related quality of life, possibly suggesting that those with an earlier onset had more opportunity to adapt or choose work conditions that were more suitable.…”
Section: Discussionmentioning
confidence: 99%
“…The most dominant factor that predicted weight gain within 3 years in every age and race subgroup was weight change in the past 2 years. Recent studies showed that in postmenopausal women, after weight-loss intervention, weight regain was associated with weight gain after menopause[ 3 , 37 ], indicating that positive weight change (i.e., weight gain) after menopause was a risk factor of regaining weight. Our novel finding was that 5 kg weight fluctuations (including weight gain as well as weight loss) during the past 2 years were related to gaining ≥3% weight at AV3.…”
Section: Discussionmentioning
confidence: 99%